2019
DOI: 10.1515/secm-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste Eggshells addition on Microstructures, Mechanical and Tribological Properties of Green Metal Matrix Composite

Abstract: Chicken eggshell (Es) waste is an industrial byproduct, and its disposal constitutes a severe environmental risk. Eggshell is a new engineering reinforcement retaining excellent properties such as low density, renewable, eco-friendly, and high thermal stability. The current research aims to study the effects of eggshell particles addition on microstructures, mechanical and tribological properties of aluminium/eggshell green metal matrix composites (MMCs). In the present work Al–Es metal matrix composite is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
4
8
0
Order By: Relevance
“…According to the microstructure analysis, the matrix exhibits a homogeneous reinforcement distribution. The findings are consistent with those of previous studies (Agunsoye et al, 2015;Hayajneh et al, 2019;Bhoopathi and Ramesh, 2020), who found that when the concentration (Wt.%) of reinforcing particles increases beyond a certain threshold, ductility decreases. Drop in ductility of 65.7% was achieved at 20% of the reinforcement's brittle and hard ceramic particles (ESA and RHA reinforcing particles).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…According to the microstructure analysis, the matrix exhibits a homogeneous reinforcement distribution. The findings are consistent with those of previous studies (Agunsoye et al, 2015;Hayajneh et al, 2019;Bhoopathi and Ramesh, 2020), who found that when the concentration (Wt.%) of reinforcing particles increases beyond a certain threshold, ductility decreases. Drop in ductility of 65.7% was achieved at 20% of the reinforcement's brittle and hard ceramic particles (ESA and RHA reinforcing particles).…”
Section: Resultssupporting
confidence: 93%
“…Reinforcing particles can be more evenly distributed and dispersed using the stir casting method. Reinforcement particulates are spread evenly all across the matrix, which is consistent with prior studies (Agunsoye et al , 2015; Hayajneh et al , 2019; Bhoopathi and Ramesh, 2020) based on microstructure investigation. Particles distribution and dispersion reinforcement can be greatly improved by casting in an electromagnetic field.…”
Section: Resultssupporting
confidence: 88%
“…Mondal et al [46] stated that with the reinforcement particles addition, composites sticking tendency with the counterface is reduced and resulted in improved wear resistance of the composites when compared with the base alloy. Similar behaviour has been observed in different studies where the reduction in wear loss was reported with the reinforcement particles addition [15,19,20].…”
Section: Effect Of Esa and B 4 C Particles On Wearsupporting
confidence: 90%
“…It was concluded that ES particles help to improve the composites wear resistance as indicated by analysis of variance. Hayajneh et al [20] investigated the effect of waste ES reinforcement on the mechanical and tribological characteristics of Al matrix composites and found that incorporation of 3 wt.% ES improved the wear resistance, compressive strength and hardness by 65%, 40% and 15%, respectively. Further increase in wt.% of ES has an adverse effect on the mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest value of COF was obtained for a variant with 4 wt % of filler. However, in the case of higher waste contents, a negative effect was observed, which was explained by the increase in porosity and agglomeration of particles [ 46 ]. In another study, Dwiwedi et al investigated the influence of eggshell reinforcement (0–10 wt %) on the composites based on the Al6061 aluminum alloy matrix [ 47 ].…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%